Bar-driven Streaming Motions Mimic a Massive Bulge in the Inner Milky Way - Junichi Baba (The Astrophysical Journal)
The circular speed curve of the Milky Way provides a key constraint on its mass distribution, reflecting the axisymmetric component of the gravitational potential. This is especially critical in the inner Galaxy ( R  ≲ 4 kpc), where nonaxisymmetric structures, such as the stellar bar and nuclear stellar disk, strongly influence dynamics. However, significant discrepancies remain between circular speed curves inferred from stellar dynamical modeling and those derived from the terminal-velocity method applied to gas kinematics. To investigate this, we perform three-dimensional hydrodynamic simulations including cooling, heating, star formation, and feedback, under a realistic gravitational potential derived from stellar dynamical models calibrated to observational data. This potential includes the Galactic bar, stellar disks, dark matter halo, nuclear stellar disk, and nuclear star cluster. We generate synthetic longitude–velocity diagrams and apply the terminal-velocity method to derive circular speeds. The simulated gas reproduces the observed terminal-velocity envelope, including a steep inner rise. We find this feature arises from bar-driven noncircular motions, which cause the terminal-velocity method to overestimate circular speeds by up to a factor of 2 at R  ∼ 0.4 kpc, and enclosed mass by up to a factor of 4. These results suggest that inner gas-based rotation curves can significantly overestimate central mass concentrations. The steep inner rise in gas-derived circular speeds does not require a massive classical bulge but can be explained by bar-induced streaming motions. Rather than proposing a new mechanism, our study provides a clear, Milky Way–specific demonstration of this effect, emphasizing the importance of dynamical modeling that explicitly includes noncircular motions for accurate mass inference in the inner Milky Way.